Petrophysics Analysis For Determining The Prospect Zone Of A Hydrocarbon Reservoir In The “X” Field Of The Cekungan Banggai - Abduh, Muh (Alpatih Harapan Semesta, 2023)
This study aims to determine the hydrocarbon reservoir zones in the ABD-1, ABD-2 and ABD-3 fields which are analyzed using quantitative and qualitative analysis to determine reservoir properties involving gamma ray (GR) log data, neutron log (NPHI) and log density (RHOB). The stage of determining the hydrocarbon content using resistivity log data, NPHI log and RHOB log. Determination of reservoir zones of hydrocarbon reservoirs using resistivity log data analysis and NPHI log data. The quantitative analysis in this study calculates the value of shale volume (Vshale), porosity (Ф), resistivity (RW) and water saturation (SW). The research results obtained from quantitative analysis using the ABD-1 well at depths of 7422 ft -7426 ft, 7869 ft - 7924 ft, 8033 ft - 8100 ft are able to determine the percentage of hydrocarbons contained in the zone. For gas, the value of Sw is 0 – 35, oil has a value of Sw, which is 35 – 65, and water has a price, Sw, which is 65. These percentages cannot be used as a benchmark for the assumption of hydrocarbons containing oil and gas, because if the price of Sw is 35, it could be oil. or vice versa. If using qualitative analysis it is found that the reservoir zone at a depth of 7422 ft – 7426 ft is a gas-containing hydrocarbon. At depths of 7638 ft – 7730 ft are gaseous hydrocarbons. Reservoirs at a depth of 7422 ft – 7426 ft are water-containing hydrocarbons.